Mixed-etiology leg ulcers in a patient on long-term glucocorticoid therapy - Piotr Sławiński; Marcin Radkowski; Andrzej Lewandowicz; Tomasz Targowski (Rheumatology, 2019)
Chronic leg ulceration is a frequent condition in elderly patients. Chronic wounds that are nonresponsive to 3-month therapy affect approximately 6.5 million people in the United States with a prevalence of 1% and costs estimated at 25 billion dollars per year. Although the main causes are venous insufficiency, lower extremity arterial disease and diabetes, in many cases the etiology is multi-factorial. Approximately 20–23% of non-healing wounds that are refractory to vascular intervention have other etiologies including vasculitis, rheumatoid arthritis and Sjögren syndrome. Adverse drug interactions are the least commonly considered, especially those which involve disease-modifying anti-rheumatic drugs. The authors present a report on a female patient with reported Sjögren syndrome, multiple morbidities and non-healing lower limb ulceration that developed during treatment with methotrexate, and no significant improvement after discontinuation of the drug and after vascular surgery. Microvascular deterioration caused by beta-blockers was considered decisive. Calcium-blocker replacement brought complete healing in the follow-up.